Modern principles and problems of degradation of cultivated ameliorated soils - Bandurin Mikhail (EDP Sciences, 2021)
The paper considers modern principles and problems of degradation of cultivated ameliorated soils. The current problem of the use of the planet’s land resources is that food and fiber production are annually reduced by soil loss and degradation, primarily as a result of human activities. There are many reasons for this dangerous phenomenon, and they differ in different natural and socio-economic conditions. But the end result is always the same everywhere: either a drop in fertility or the loss of the soil itself. Currently, about 7 million hectares of arable land, i.e. the base of life for 21 million people is irrevocably annually lost in the world as a result of various processes of degradation and alienation, with the current norm of 0.3 hectares per 1 person.